Isolation and Dignosis of Penicillium Expansum from the Cosmetics Which Ability to Produce Patulin and using Zinc Oxide Nanoparticles as Antifungal Compound - R. A. Sahib (Journal of Global Pharma Technology, 2019)
In this study Penicillium expansum was isolated from the cosmetic samples, 50 cosmetic samples which were used such as (eye shadow, face cream, face mask, lipstick and hand cream). The sabouraud dextrose agar was used to test the presence of P. expansum. Thin layer chromatography (TLC) was appeared yellow spots of patulin toxin with rate of flow (RF) is 76% under UV light exposure.The UV-visible spectroscopy result proved the wavelength of patulin is located with 270 nm and 1.8 absorbance.High performance liquid chromatography (HPLC) results show that retention time of major peak of standard patulin and a filter extract of P. expansum are located at (15 and 15.1) min, respectively, which are located in the same area. Zinc oxide nanoparticles using as a fungicide to control development growth of P. expansum which proved high efficiency to decrease growth of P. expansum by percentage of (33,50,77) % respectively in the concentration (2,4,6) mmol/L, while 8 mmol/L of ZnO caused complete inhibition growth of P. expansum as compared with the control group which untreated with ZnO NPs. Scanning electron microscopy (SEM) images show that ZnO NPs caused decreased with disrupted of conidia and decreased number of mycelium.Keywords: Penicillium expansum, Cosmetics, UV-vis, HPLC, SEM, Zinc oxide nanoparticles.